A self-repair history: compensatory effect of a de novo variant on the FANCA c.2778+83C>G splicing mutation - Persico, Ilaria; Fontana, Giorgia; Faleschini, Michela; Zanchetta, Melania Eva; Ammeti, Daniele; Cappelli, Enrico; Corsolini, Fabio; Mosa, Clara; Guarina, Angela; Bogliolo, Massimo; Surrallés, Jordi; Dufour, Carlo; et al. (Frontiers in Genetics, 2023)
Fanconi anemia (FA) is a genome instability condition that drives somatic mosaicism in up to 25% of all patients, a phenomenon now acknowledged as a good prognostic factor. Herein, we describe the case of P1, a FA proband (P1) carrying a splicing variant, molecularly compensated by a de novo insertion. Targeted next generation sequencing on P1’s peripheral blood DNA detected the known FANCA c.2778+83C>G intronic mutation and suggested the presence of a large deletion on the other allele, then assessed by MLPA and RT-PCR. To determine c.2778+83C>G splicing effect, we performed a RT-PCR on P1’s lymphoblastoid cell line (LCL), and on the LCL of another patient (P2) carrying the same variant. Although in P2 we confirmed the expected alternative spliced form with a partial intronic retention, we detected no aberrant products in P1’s sample. Sequencing of P1’s LCL DNA allowed to identify the de novo c.2778+86insT variant, predicted to compensate 2778+83C>G impact. Albeit not found in P1’s bone marrow (BM) DNA, c.2778+86insT was detected in a second P1’s LCL established afterwards, suggesting its occurrence at low level in vivo. Minigene assay recapitulated the c.2778+83C>G effect on splicing and the compensatory role of c.2778+86insT in reestablishing the physiological mechanism. Accordingly, P1’s LCL under mitomycin C selection preserved FA pathway activity in terms of FANCD2 monoubiquitination and cell survival. Our findings prove c.2778+86insT role as a second site variant capable of rescuing c.2778+83C>G pathogenicity in vitro, which might contribute to a slow hematopoietic deterioration and a mild hematologic evolution.